Parallelism of Chemicostructural Properties between Filgrastim Originator and Three of Its Biosimilar Drugs - Alessandra Gianoncelli; Michela Bertuzzi; Michela Guarienti; Sara Vezzoli; Sara Anna Bonini; Andrea Mastinu; Sandra Sigala; Maurizio Memo (Journal of Chemistry)
The approval and granting of marketing authorization for a putative biosimilar is based on strong comparability studies with its biological reference product. This is due to the complexity of the structure and nature of the manufacturing process of biological drugs. Hence, a rigorous analytical workflow for chemical characterization and clinical trials to evaluate the efficacy and safety is required to demonstrate their high similarities to the reference drug. This work is focused on the comparison of the originator of filgrastim with three of its biosimilars by evaluating their structural similarity and biological activity. Qualiquantitative analyses were performed by MALDI-TOF/TOF-MS and RP-HPLC-UV. An innovative functional assay using zebrafish as the animal model was developed to evaluate the biological activities of the drugs. The different analyses performed in this study highlighted the structural similarity of biosimilar drugs and their originator. This result was further confirmed by a similar in vivo biological activity.